2014
DOI: 10.1002/ajmg.b.32229
|View full text |Cite
|
Sign up to set email alerts
|

The interaction effect between BDNF val66met polymorphism and obesity on executive functions and frontal structure

Abstract: The prevalence of obesity is increasing worldwide. Previous research has shown a relationship between obesity and both executive functioning alterations and frontal cortex volume reductions. The Brain Derived Neurotrophic Factor val66met polymorphism, involved in eating behavior, has also been associated with executive functions and prefrontal cortex volume, but to date it has not been studied in relation to obesity. Our aim is to elucidate whether the interaction between the Brain Derived Neurotrophic Factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 61 publications
3
30
0
Order By: Relevance
“…TMT_B is considered as a tool to measure working memory and executive performance such as set-shifting, inhibition and cognitive flexibility (Marqués-Iturria et al 2014). However we found no association between BDNF polymorphisms and haplotypes and other neuropsychological tests, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…TMT_B is considered as a tool to measure working memory and executive performance such as set-shifting, inhibition and cognitive flexibility (Marqués-Iturria et al 2014). However we found no association between BDNF polymorphisms and haplotypes and other neuropsychological tests, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although obesity is not usually strictly considered a brain disorder, multiple lines of neurobiological research have revealed the existence of structural and functional brain alterations associated with obesity (Dagher, 2012). Relative to normal-weight participants, obese populations exhibit lower gray matter volume, cortical thickness and glucose metabolism in the prefrontal cortex (Pannacciulli et al, 2006;Willeumier et al, 2011;Marqués-Iturria et al, 2014). In striatal structures, individuals with obesity seem to exhibit lower dopamine D2/D3 receptor availability (Wang et al, 2001;De Weijer et al, 2011; but see Eisenstein et al, 2013) and increased gray matter volume .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MRI studies displayed differences in cortex thickness between obese and non-obese Met carriers, showing that the thinnest frontal cortex areas pertained to obese subjects. This strongly suggests the connection between obesity, BDNF Val66Met and executive functions [21].…”
Section: Brain-derived Neurotrophic Factor Val66met Polymorphism In Cmentioning
confidence: 80%
“…Moreover, obesity affects the structure of the frontal lobe; obesity correlates with lowered thickness of cortical and subcortical areas. Abovementioned may be [21].…”
Section: Brain-derived Neurotrophic Factor Val66met Polymorphism In Cmentioning
confidence: 99%
See 1 more Smart Citation